Risk Factors for Surgical Site Infections in Dermatological Surgery - Xiaomeng Liu; Melissa Sprengers; Patty J. Nelemans; Klara Mosterd; Nicole W.J. Kelleners-Smeets (Medical Journals Sweden, 2017)
Current literature on risk factors for surgical site infection (SSI) in dermatological surgery in the absence of antibiotic prophylaxis is limited. The aim of this study was to retrospectively evaluate patients presenting for dermatological surgery. A total of 1,977 procedures were reviewed. SSI was clinically suspected in 79 (4.0%) patients and confirmed by culture in 38 (1.9%). Using the strictest definition of SSI (clinical symptoms with positive culture) significantly higher risk of SSI was found for location on the ear (odds ratio (OR) 6.03, 95% confidence interval (95% CI) 2.12-17.15), larger defects (OR 1.08 per cm2 increase, 95% CI 1.03-1.14), closure with flaps (OR 6.35, 95% CI 1.33-30.28) and secondary intention (OR 3.01, 95% CI 1.11-8.13). These characteristics were also associated with higher risk of clinically suspected SSI regardless of culture results with slightly lower ORs. In conclusion, the risk of acquiring a SSI is increased in surgeries performed on the ear, in larger wounds and in defects closed with flaps or healed by secondary intention.